ELECTRIC VEHICLE IN INDIA AND UNDERSTANDING THE CONSUMER PERCEPTION - Asthana, Atul (International Journal of Psychosocial Rehabilitation, 2020)
India is a country with the third-largest road network in the world. Road travel seemed to be a preferred choice in India, with over 60 % of the population using personal or shared vehicles to commute. Conventional vehicles are a major cause of global warming and environmental air pollution. All types of vehicles produce dust from brakes, tires, and road wear. The average diesel vehicle has a worse effect on air quality than the average gasoline vehicle. But both gasoline and diesel vehicles pollute more than the electric vehicle. Governments started using fiscal policies, such as road tax, to discourage the purchase and use of more polluting cars. Green tax is imposed while re-registering the vehicle after 15 years of use to make people discontinue the use of polluting vehicles and encourage them to use fuel-efficient and less polluting vehicles. The FAME India Scheme is an incentive scheme for the promotion of electric and hybrid vehicles. It aims to promote electric mobility and gives financial incentives for enhancing EV production and the creation of electric transportation infrastructure. In 2015 the Ministry of Heavy Industries and Public Enterprises launched FAME to incentivize the production and promotion of eco-friendly vehicles, including EV and hybrid vehicles.